MANAGEMENT OF WALKING PHYSICAL ACTIVITY IN ADOLESCENTS WITH OBESITY IN RT 07 RW 016 SRENGSENG SAWAH, JAGAKARSA, SOUTH JAKARTA - Nourmayansa Vidya Anggraini; Kharisma Ekva Nanda (Universitas Airlangga, 2023)
Introduction: Obesity is one of the health problems that must be handled properly because it can affect individuals of all ages, from children to adults. Obesity occurs in school-age children because it can interfere with the health and body image of the child. Some interventions are believed to help lose weight in school-age children who are obese. Self Hypnosis therapy is one intervention that has been proven to be able to lose weight. The application of nursing care aims to determine the effectiveness of Self Hypnosis therapy on weight loss in school-age children who are obese. Method: Obesity is one of the most common nutritional health problems in children and adolescents. Obesity is a serious problem and requires immediate treatment to avoid complications and adverse effects on the future of children and adolescents, both in terms of physical health and on the child's body image. In addition to diet, physical activity plays an important role in reducing the incidence of obesity. Physical activity walking is one form of obesity management that has been proven to reduce weight. This writing aims to perform the management of physical activity walking on weight loss in adolescents with obesity. Results: This intervention was given for 12 times to two teenagers in the Srengseng Sawah area, Jagakarsa, South Jakarta who had the criteria for obesity results with a BMI more than the 95th percentile. The results of the implementation for 4 weeks showed that there was a weight loss of 3.1kg for the first client and 2kg for the second client after the intervention of walking physical activity, so it can be concluded that the intervention of walking physical activity has an effect on weight loss in adolescents with obesity. Conclusion: Community nurses are expected to apply walking physical activity interventions as one of the interventions in overcoming obesity in adolescents.